Finite Element Based Optimization of Two-Way Concrete Slabs: A Comparative Study on Embodied Carbon and Cost Efficiency - Keintjem, Militia; Suwondo, Riza; Suangga, Made (Engineering, Technology & Applied Science Research, 2025)
The building sector is a major source of Global Greenhouse Gas (GHG) emissions. The carbon embodied in construction materials has drawn attention in sustainable design. Reinforced concrete slabs, as core structural elements, contribute notably to both environmental and economic impacts. This study examines the use of Finite Element Modeling (FEM) in the design of two-way concrete slabs. The goal is to reduce the embodied carbon and material cost compared to the conventional design methods. A concrete slab system was analysed under typical office building loads. A structural design was developed using FEM and compared to the Marcus method. This traditional approach relies on empirical moment coefficients and is widely used in Indonesian engineering practice. The results showed that FEM consistently required less reinforcement for all slab thicknesses studied. This reduction in material led to carbon savings of up to 12%. It also resulted in cost savings of up to 15% per m², especially for slabs 150–180 mm thick. While the difference between the methods decreased with thicker slabs, FEM remained more efficient in all cases. Overall, the findings show that FEM improves the structural precision. At the same time, it supports both the environmental and economic goals in slab design. Performance-based methods, like FEM, can help achieve low-carbon construction without compromising safety or code compliance.